Synchronous Paleo-Tethys closure in northern Iran: Constraints from Paleozoic-Mesozoic sediments in the western Alborz - Yiyang Lei; Yang Chu; Mark B. Allen; Wei Lin; Bo Wan; Ling Chen; Morteza Talebian; Guangyao Xin; Tanjie Liu; Yilin Guo; Lin Guo; Ranran Xia (Journal of Asian Earth Sciences, 2026)

A Mesozoic orogenic plateau across South China - Mark B. Allen; Shuguang Song; Chao Wang; Renyu Zeng; Yang Chu; Alex Copley (Earth-Science Reviews, 2026)

Late Paleoproterozoic adakitic, A-type complexes and mafic dykes in Yinshan Block, NCC: insights into long-lived orogen collapse after assembly of Columbia supercontinent - Shabbir Jawad; Shuguang Song; Yuanyuan Liu; Chao Wang; Mark B. Allen; Chunjing Wei (Precambrian Research, 2026)

Genomic connectivity and future climate suitability of the Caribbean king crab (Maguimithrax spinosissimus) highlight its potential for coral reef restoration - Pedro A. Peres; Natalie A. Whitaker-Allen; Mark J. Butler; Heather D. Bracken-Grissom (Conservation Genetics, 2026)

Immune checkpoint inhibitor-induced myasthenia gravis and myocarditis: a fatal immune-related adverse event - Whitney Main Allen; Mark Megaly; Pamrai Sharma (Immunologic Research, 2026)

Rise of oxidation and hydration in Neoarchean crust-building magmas caused by subduction (North China Craton) - Yuan-Yuan Liu; Chao Wang; Mark B. Allen; Hongyu Zhang; Li Su; Shuguang Song (Chemical Geology, 2026)

High-Resolution Diffusion Tensor Imaging of the Cerebellum and Brainstem in Chiari Malformation Type I: Association with Cognitive Function and Pain - James R. Houston; Tiffany D. Rogers; Tara M. Kirkpatrick; Anna M. Robison; Allison G. Throm; Shaun M. Burgess; Petra M. Klinge; Ken Sakaie; Sarel J. Vorster; Mark G. Luciano; Francis Loth; Philip A. Allen (The Cerebellum, 2026)

Early Paleoproterozoic Daqingshan bimodal igneous complex in the Yinshan Block of NCC: Insights into post-collisional magmatism of a Neoarchean orogen - Shabbir Jawad; Shuguang Song; Yuanyuan Liu; Yanguang Li; Chao Wang; Mark B. Allen; Chunjing Wei (Precambrian Research, 2026)

Investigating the origins of quarry populations of the Caribbean King Crab (Maguimithrax spinosissimus) to inform coral reef recovery efforts in the Florida Keys, Florida (USA) - Natalie A. Whitaker-Allen; Pedro A. Peres; Mark J. Butler; Heather D. Bracken-Grissom (Coral Reefs, 2026)

Coronary CT Angiography-Based Prediction Model for Hemodynamically Significant Coronary Stenosis Integrating Morphological and Plaque Characteristics - Chenxi Wang; Shuang Leng; Ru-San Tan; Ping Chai; Jiang Ming Fam; Adrian Fatt Hoe Low; Lohendran Baskaran; Lynette Teo; Felix Yung Jih Keng; Chee Yang Chin; Ching Ching Ong; John C. Allen; et al. (Cardiovascular Engineering and Technology, 2026)

The effects of hydroelasticity on stringer-stiffened composite panels in water impacts: An experimental study - Connor Pearson; Nicola Shepherd; Mark Battley; Tom Allen (Ocean Engineering, 2026)

Evaluation of phytogenic product supplementation on the growth performance, immune function, and gut microbiota composition in fingerling channel catfish (Ictalurus punctatus) - Ishini A. Appuhami; D. Allen Davis; Yoonhang Lee; Abdulmalik A. Oladipupo; Brent M. Vuglar; Fernando Y. Yamamoto; Mark Farmer; Timothy J. Bruce (Animal Feed Science and Technology, 2026)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Sclerochronological age synchrony corroborates remarkable lifespan and protracted asymptotic growth for a deepwater snapper (Pristipomoides zonatus) in the Indian and Pacific Oceans - Corey B. Wakefield; Joyce J.L. Ong; Ashley J. Williams; Brett M. Taylor; Allen H. Andrews; Mark Burton; Simon J. Nicol; Stephen J. Newman (Fisheries Research, 2025)

Release of oxygen (oxidized fluids) by growth of ferromanganese garnets and oxygen circulation in subduction zone - Shuguang Song; Shiting Ye; Ming Tang; Heidi E. Höfer; Mark B. Allen; Xiaoli Li (Science Bulletin, 2025)

Food-level predictors of self-reported liking and hedonic overeating: Putting ultra-processed foods in context - Graham Finlayson; Rebecca Allen; Angelika Baaij; Kristine Beaulieu; Nicola J. Buckland; Clarissa Dakin; Michelle Dalton; Ruairi O'Driscoll; Cristiana Duarte; Catherine Gibbons; Mark Hopkins; Graham Horgan; et al. (Appetite, 2025)

Influence of dietary fermented yeast products (Saccharomyces cerevisiae) on performance, health and microbiome of Nile tilapia (Oreochromis niloticus) and the influence of discharge water in the production of romaine lettuce (Lactuca sativa) - Uthpala M. Padeniya; D. Allen Davis; Daniel E. Wells; Courtney E. Harrison; Benjamin R. LaFrentz; Benjamin H. Beck; Luke A. Roy; Mark Farmer; Timothy J. Bruce (Animal Feed Science and Technology, 2025)

Popcorn stand reduction in the United States Midwest: Insights on plant traits and grain yield - I.P. Lisboa; A.J. McMechan; R.W. Elmore; C.A. Proctor; Allen Geyer; Peter Thomison; Alexander Lindsey; Mark Zarnstorff; James Houx; O.A. Ortez (Field Crops Research, 2025)

Salt marsh grass for reducing overtopped flow momentum: Experimental results and XBeach calibration - Joshua Bagg; Mark Battley; Colin Whittaker; Tom Allen; Tom Shand (Coastal Engineering, 2025)

Long-lived mantle plume trail recorded the onset and spreading of the Proto-Tethys Ocean - Jinran Qiao; Jie Dong; Li Su; Mark B. Allen; Shuguang Song (Science Bulletin, 2025)

Jurassic picritic and potassic mafic dyke swarms in eastern China: Evidence for thermal erosion of the lithospheric mantle during Paleo-Pacific subduction - Wenjia Wang; Shuguang Song; Chao Wang; Mark B. Allen; Lifei Zhang; Xiaowei Li; Li Su (Gondwana Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Isotopically resolved fate and processes of nitrogen in a constructed wetland treating domestic effluent - Danielle J. Allen; Mark Farrell; Wei Wen Wong; Jianyin Huang; Luke M. Mosley (Science of The Total Environment, 2025)

Using seasonal palaeo-flow reconstructions and artificial neural networks for daily water balance modelling: A case study from Tasmania, Australia - Danielle C. Verdon-Kidd; Kathryn J. Allen; Luke J. Kidd; Carolyn Maxwell; Mark Willis; Patrick Baker (Global and Planetary Change, 2025)

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Harvest trends, growth and longevity, and population dynamics reveal traditional assumptions for redhorse (Moxostoma spp.) management in Minnesota are not supported - Alec R. Lackmann; Ewelina S. Bielak-Lackmann; Reed I. Jacobson; Allen H. Andrews; Malcolm G. Butler; Mark E. Clark (Environmental Biology of Fishes, 2024)

Rise of mantle oxidation by Neoarchean subduction in the North China Craton - Zhenzhu Wu; Chao Wang; Mark B. Allen; Ming Tang; Yi Chen; Lihui Jia; Shuguang Song (Earth and Planetary Science Letters, 2024)

Assessment of dietary yeast‐based additives for cultured catfish and tilapia health - Guillaume Cacot; D. Allen Davis; Benjamin R. LaFrentz; Mark R. Liles; Ian A. E. Butts; Craig A. Shoemaker; Benjamin H. Beck; Mark Farmer; Timothy J. Bruce (Journal of Fish Diseases, 2024)
Channel catfish ( Ictalurus punctatus ) and Nile tilapia ( Oreochromis niloticus ) are two aquaculture species of great importance. Intensive production is often hindered by poor growth performance and disease mortality. The aim of this study was to evaluate the potential of a commercial fermented yeast product, DVAQUA, on channel catfish and Nile tilapia growth performance metrics and disease resistance. Channel catfish and Nile tilapia were fed practical diets supplemented with 0%, 0.1% or 0.4% of DVAQUA over approximately 2‐month feeding periods in recirculation aquaculture systems. To assess the potential of the postbiotic against common aquaculture pathogens, juvenile catfish were subsequently challenged by immersion with Edwardsiella ictaluri S97‐773 or virulent Aeromonas hydrophila ML09‐119. Nile tilapia juveniles were challenged by injection with Streptococcus iniae ARS‐98‐60. Serum lysozyme activity, blood chemistry and growth metrics were measured at the end of the feeding period, but no differences were observed across the different metrics, except for survival. For the pathogen challenges, there were no differences in endpoint mortality for channel catfish with either pathogen ( p > .05). In contrast, Nile tilapia survivability to S. iniae infection increased proportionally to the inclusion of DVAQUA ( p = .005). Changes to sera lysozyme activity were also noted in the tilapia trial, with a reduction of activity in the fish fed the 0.4% DVAQUA diet compared to the control diet ( p = .031). Expression profiles of proinflammatory genes and antibodies were also found to be modulated in channel catfish fed the postbiotic, indicating some degree of protective response. These results suggest that this postbiotic may be beneficial in protecting Nile tilapia against S. iniae infection by influencing immune parameters and additional research is needed to evaluate the potential of this DVAQUA for improving catfish health and disease control.

Mesoscale Brain Mapping: Bridging Scales and Modalities in Neuroimaging – A Symposium Review - Joshua K. Marchant; Natalie G. Ferris; Diana Grass; Magdelena S. Allen; Vivek Gopalakrishnan; Mark Olchanyi; Devang Sehgal; Maxina Sheft; Amelia Strom; Berkin Bilgic; Brian Edlow; Elizabeth M. C. Hillman; et al. (Neuroinformatics, 2024)
Advances in the spatiotemporal resolution and field-of-view of neuroimaging tools are driving mesoscale studies for translational neuroscience. On October 10, 2023, the Center for Mesoscale Mapping (CMM) at the Massachusetts General Hospital (MGH) Athinoula A. Martinos Center for Biomedical Imaging and the Massachusetts Institute of Technology (MIT) Health Sciences Technology based Neuroimaging Training Program (NTP) hosted a symposium exploring the state-of-the-art in this rapidly growing area of research. “Mesoscale Brain Mapping: Bridging Scales and Modalities in Neuroimaging” brought together researchers who use a broad range of imaging techniques to study brain structure and function at the convergence of the microscopic and macroscopic scales. The day-long event centered on areas in which the CMM has established expertise, including the development of emerging technologies and their application to clinical translational needs and basic neuroscience questions. The in-person symposium welcomed more than 150 attendees, including 57 faculty members, 61 postdoctoral fellows, 35 students, and four industry professionals, who represented institutions at the local, regional, and international levels. The symposium also served the training goals of both the CMM and the NTP. The event content, organization, and format were planned collaboratively by the faculty and trainees. Many CMM faculty presented or participated in a panel discussion, thus contributing to the dissemination of both the technologies they have developed under the auspices of the CMM and the findings they have obtained using those technologies. NTP trainees who benefited from the symposium included those who helped to organize the symposium and/or presented posters and gave “flash” oral presentations. In addition to gaining experience from presenting their work, they had opportunities throughout the day to engage in one-on-one discussions with visiting scientists and other faculty, potentially opening the door to future collaborations. The symposium presentations provided a deep exploration of the many technological advances enabling progress in structural and functional mesoscale brain imaging. Finally, students worked closely with the presenting faculty to develop this report summarizing the content of the symposium and putting it in the broader context of the current state of the field to share with the scientific community. We note that the references cited here include conference abstracts corresponding to the symposium poster presentations.

A subduction-dismembered Neoproterozoic large igneous province in the Qinling Orogenic Belt, China: Implications for 850 Ma–initiated mantle plume activity in the greater Yangtze Block - Di Feng; Lu Xiong; Chao Wang; Mark B. Allen; Jie Dong; Chunjing Wei; Li Su; Shuguang Song (Precambrian Research, 2024)

Abundance, production, and migrations of nesting green turtles at Rose Atoll, American Samoa, a regionally important rookery in the Central South Pacific Ocean - Shawn K. Murakawa; Alexander R. Gaos; Devin S. Johnson; Brian Peck; Mark MacDonald; Elyse Sachs; Frank Pendleton; Camryn D. Allen; Marylou K. Staman; Shelbie Ishimaru; Kyle S. Van Houtan; Alphina Liusamoa; et al. (Frontiers in Marine Science, 2024)
Sea turtles are a taxon of conservation concern and are highly migratory, exposing them to a variety of threats (e.g., fisheries bycatch, direct harvest) across their lifetime. Understanding the abundance of nesting females, hatchling production, and migratory movements - three of the most basic biological data needs for this species group - is imperative for population assessment. This study summarizes novel data most relevant to population assessments of the endangered central south Pacific (CSP) green turtle ( Chelonia mydas ) population, determined from annual rapid assessment surveys (mean survey duration=7.6 days year -1 , n=61 survey days over 8 nesting seasons) and satellite telemetry at Rose Atoll, American Samoa, from 2012 to 2019. A minimum of 138 unique females nested in the Rose Atoll National Wildlife Refuge (RANWR) over the study period with 218 total females observed. Satellite tracks of post-nesting females suggest Fiji (n=33/48, 70.2%) is the primary foraging ground for turtles nesting at RANWR, though other areas throughout the south Pacific Ocean are also important. Limited data suggest hatchling production was high (average hatching success=92.3%) and nest temperature data collected from 2017-2019 suggest primary sex ratios were likely balanced during this time. These are positive signs for the resilience of this nesting population, but climate change poses threats to RANWR and other low-lying tropical islands throughout the central south Pacific, as nesting areas are potentially exposed to beach erosion, tidal inundations, and increasing temperatures leading to sex bias and embryonic death.

On the influence of flow-front orientation on stringer stiffened composite panels in water impacts - Connor Pearson; Marius de Mourgues; Mark Battley; Veronique Michaud; John Little; Guillaume Verdier; Tom Allen (Ocean Engineering, 2024)

Evaluation of 90-day repeated dose oral toxicity of an aloe vera inner leaf gel beverage - A. Wallace Hayes; Peter Pressman; Roger Clemens; Allen W. Singer; Mark R. Bauter (Food and Chemical Toxicology, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Subduction zone decoupling and rapid forearc spreading at an active continental margin: Evidence from an SSZ-type ophiolite in Qilian Orogen, NW China - Jinran Qiao; Jie Dong; Mark B. Allen; Li Su; Shuguang Song (Journal of Asian Earth Sciences, 2024)

Geometry, slip rate, and the latest earthquake of the Jinta Nanshan Fault: Interactions of the Altyn Tagh Fault and the Qilian Shan at the northern margin of the Tibetan Plateau - Bo Zhang; Mark B. Allen; Yunsheng Yao; Junwen Zhu; Ming Wu; Weitong Wang; Yameng Wen; Wengui He; Zhongsheng Lei; Wei Pang (Tectonophysics, 2024)

Garnet zoning patterns record multiple processes of chemical transfer during subduction - Freya R. George; Daniel R. Viete; Janaína Ávila; Gareth G.E. Seward; George L. Guice; Mark B. Allen; Michael J. Harrower (Earth and Planetary Science Letters, 2024)

Tracing DUPAL anomaly evolution in the Tethyan-Indian oceanic mantle - Chao Wang; Shuguang Song; Guochun Zhao; Mark B. Allen; Li Su; Lukáš Ackerman; Jiří Sláma; Donghai Zhang; Tao Wen; Di Feng; Ladislav Strnad (Geochimica et Cosmochimica Acta, 2024)

Population genomic structure of a widespread, urban‐dwelling mammal: The eastern grey squirrel ( Sciurus carolinensis ) - Nicole A. Fusco; Bradley J. Cosentino; James P. Gibbs; Maximilian L. Allen; Alexander J. Blumenfeld; George H. Boettner; Elizabeth J. Carlen; Merri Collins; Catherine Dennison; Devin DiGiacopo; André‐Philippe Drapeau Picard; Jonathan Edmonson; et al. (Molecular Ecology, 2024)
Urbanization is a persistent and widespread driver of global environmental change, potentially shaping evolutionary processes due to genetic drift and reduced gene flow in cities induced by habitat fragmentation and small population sizes. We tested this prediction for the eastern grey squirrel ( Sciurus carolinensis ), a common and conspicuous forest‐dwelling rodent, by obtaining 44K SNPs using reduced representation sequencing (ddRAD) for 403 individuals sampled across the species' native range in eastern North America. We observed moderate levels of genetic diversity, low levels of inbreeding, and only a modest signal of isolation‐by‐distance. Clustering and migration analyses show that estimated levels of migration and genetic connectivity were higher than expected across cities and forested areas, specifically within the eastern portion of the species' range dominated by urbanization, and genetic connectivity was less than expected within the western range where the landscape is fragmented by agriculture. Landscape genetic methods revealed greater gene flow among individual squirrels in forested regions, which likely provide abundant food and shelter for squirrels. Although gene flow appears to be higher in areas with more tree cover, only slight discontinuities in gene flow suggest eastern grey squirrels have maintained connected populations across urban areas in all but the most heavily fragmented agricultural landscapes. Our results suggest urbanization shapes biological evolution in wildlife species depending strongly on the composition and habitability of the landscape matrix surrounding urban areas.

Hydrodynamic response to bathymetric changes in Tampa Bay, Florida - Jing Chen; Yonggang Liu; Robert H. Weisberg; Steven A. Murawski; Sherryl Gilbert; David F. Naar; Lianyuan Zheng; Matthew Hommeyer; Catherine Dietrick; Mark E. Luther; Cheryl Hapke; Edward Myers; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Novel insight into ammonium, phosphate, and iron(II) dynamics in the sediment porewater of a constructed wetland under artificial aeration through the diffusive equilibrium in thin films technique - Danielle J. Allen; Jianyin Huang; Mark Farrell; Luke M. Mosley (Environmental Research, 2023)

Probiotics enhance resistance to Streptococcus iniae in Nile tilapia ( Oreochromis niloticus ) reared in biofloc systems - Uthpala Padeniya; D. Allen Davis; Mark R. Liles; Stacey A. LaFrentz; Benjamin R. LaFrentz; Craig A. Shoemaker; Benjamin H. Beck; Daniel E. Wells; Timothy J. Bruce (Journal of Fish Diseases, 2023)
Biofloc technology is a rearing technique that maintains desired water quality by manipulating carbon and nitrogen and their inherent mixture of organic matter and microbes. Beneficial microorganisms in biofloc systems produce bioactive metabolites that may deter the growth of pathogenic microbes. As little is known about the interaction of biofloc systems and the addition of probiotics, this study focused on this integration to manipulate the microbial community and its interactions within biofloc systems. The present study evaluated two probiotics ( B. velezensis AP193 and BiOWiSH FeedBuilder Syn 3) for use in Nile tilapia ( Oreochromis niloticus ) culture in a biofloc system. Nine independent 3785 L circular tanks were stocked with 120 juveniles (71.4 ± 4.4 g). Tilapia were fed for 16 weeks and randomly assigned three diets: a commercial control diet or a commercial diet top‐coated with either AP193 or BiOWiSH FeedBuilder Syn3. At 14 weeks, the fish were challenged with a low dose of Streptococcus iniae (ARS‐98‐60, 7.2 × 10 7 CFU mL −1 , via intraperitoneal injection) in a common garden experimental design. At 16 weeks, the fish were challenged with a high dose of S. iniae (6.6 × 10 8 CFU mL −1 ) in the same manner. At the end of each challenge trial, cumulative per cent mortality, lysozyme activity and expression of 4 genes ( il‐1β , il6 , il8 and tnfα ) from the spleen were measured. In both challenges, the mortalities of the probiotic‐fed groups were significantly lower ( p S. iniae . Nonetheless, overall il6 expression was lower in fish challenged with a high dose of ARS‐98‐60, while tnfα expression was lower in fish subjected to a lower pathogen dose. Study findings demonstrate the applicability of probiotics as a dietary supplement for tilapia reared in biofloc systems.

The Clacton-on-Sea (Essex, UK) GCR site and SSSI: New data and continuing importance - Tom S. White; David R. Bridgland; Peter Allen; Mark J. White (Proceedings of the Geologists' Association, 2023)

Quaternary Earth-science and Palaeolithic conservation initiatives in the Tejo (Tagus), Portugal: Comparison with the Lower Thames, UK - Pedro Proença Cunha; David R. Bridgland; Silvério Figueiredo; António A. Martins; Peter Allen; Mark J. White (Proceedings of the Geologists' Association, 2023)

Assessment of filter subsampling and extrapolation for quantifying microplastics in environmental samples using Raman spectroscopy - Dounia El Khatib; Troy D. Langknecht; Michaela A. Cashman; Mark Reiss; Kelly Somers; Harry Allen; Kay T. Ho; Robert M. Burgess (Marine Pollution Bulletin, 2023)

Inferring inter-colony movement within metapopulations of yellow-footed rock-wallabies using estimates of kinship - Deane A. Smith; Mark R. Lethbridge; Benjamin L. Allen; Rose L. Andrew (Conservation Genetics, 2023)
Understanding the exchange of individuals between wildlife populations, particularly those with naturally fragmented habitats, is important for the effective management of these species. This is of particular consequence when the species is of conservation concern, and isolated populations may be lost due to pressures from predation or competition, or catastrophic events such as wildfire. Here we demonstrate the use kinship and population structure analysis to show potential recent movement between colonies in metapopulations of yellow-footed rock-wallaby ( Petrogale xanthopus Gray 1854) at two sites in the Grey Range of Queensland, and at four sites in the Gawler Ranges of South Australia. These colonies are also compared to a single colony from the Flinders Ranges, a connected landscape of rock-wallaby habitat. Using reduced representation next-generation sequencing, we acquired and filtered a set of ~ 17,000 single-nucleotide polymorphisms to examine population genetic variation, structure and relationships within populations, and also identify putative migrants. Initial STRUCTURE analysis re-confirmed each population should be considered separately. Tests of population genetic variation identify several colonies appearing to be experiencing genetic erosion, also with low calculated effective population sizes (N e = 4.5–36.6). Pairwise comparisons of individual relatedness (relatedness coeffiecients; r ) implied several contemporary movement events between colonies within both the Gawler and Grey Ranges ( r > 0.125), which was then affirmed with tests for putative first generation migrants. These results are of particular note in South Australia, where threat abatement (management of key predators and competitors) may facilitate dispersion. Additionally, in Queensland, colonies are separated by anthropogenic barriers: predator exclusion fencing designed to exclude dingoes ( Canis familiaris ) from grazing land, which may hinder dispersal. This work highlights the usefulness of population genetics to inform management outcomes in wildlife, in this case, highlighting the need for threatened species management at the landscape level.

An oblique subduction model for closure of the Proto-Tethys and Palaeo-Tethys oceans and creation of the Central China Orogenic Belt - Mark B. Allen; Shuguang Song; Chao Wang; Renyu Zeng; Tao Wen (Earth-Science Reviews, 2023)

A framework for functional fish passage decision-making - Rebecca Dolson; R. Allen Curry; Philip M. Harrison; Gordon Yamazaki; Tommi Linnansaari; Mark MacNevin; David L. G. Noakes (Environmental Biology of Fishes, 2023)

Oyster aquaculture cages provide fish habitat similar to natural structure with minimal differences based on farm location - Renee Mercaldo-Allen; Peter J. Auster; Paul Clark; Mark S. Dixon; Erick Estela; Yuan Liu; Lisa Milke; Gillian Phillips; Dylan Redman; Barry C. Smith; Alison Verkade; Julie M. Rose (Frontiers in Marine Science, 2023)
Oyster aquaculture gear may augment natural seafloor by providing structured habitat for economically important fish species. Underwater video census was used to assess fish abundance and community composition on eastern oyster ( Crassostrea virginica ) shelf and bag style aquaculture off-bottom cages and within natural rock reef habitat. During 2018, underwater cameras were mounted on four study cages at a dense shellfish farm of 40-100 commercial cages (dense cage farm), on four single cages interspersed on low relief seafloor (sparse cage farm), and amongst four boulders on a rock reef (rock reef), within an embayment off Milford, Connecticut, which is part of Long Island Sound, in the United States. In 2019, cameras were similarly deployed on two study cages per farm at each of three shellfish farms off Milford, Norwalk and Westport, CT. Video was recorded hourly in eight-minute segments from 7 am to 7 pm. Data loggers monitored seawater temperature, light intensity, and current speed. Fish abundance (MaxN) was calculated for all videos. We compared fish abundance and community composition between May and September, on cage and boulder habitat, on cages at dense and sparse farms and on cages across farm locations. In 2018, abundance of black sea bass ( Centropristis striata ), scup ( Stenotomus chrysops ) and tautog ( Tautoga onitis ) was significantly higher on cages than boulders, regardless of cage number. Cunner ( Tautogolabrus adspersus ) abundance was significantly higher on boulders than cages when cage sites were grouped. However pairwise comparisons indicated that cunner were significantly higher at the sparse cage farm versus the rock reef but cunner abundance on the dense cage farm and rock reef sites was not significantly different. Abundance of black sea bass, scup, tautog, and cunner were not significantly different across 2019 farm locations. Young-of-the-year fish occurred episodically at all sites during both years, with black sea bass and scup most abundant. Fish abundance corresponded to seasonal changes in seawater temperature and was highest at the warmest temperatures. Light intensity and current speed explained less variation in fish abundance relative to temperature, and relationships were inconsistent across habitats and farm locations Our results suggest that multi-tiered oyster aquaculture cages contribute structure to seafloor environments that provide habitat for temperate reef fish similar to natural rock reefs.

Syn- and post-collisional potassic to ultrapotassic alkaline and subalkaline volcanic rocks: Heterogeneous mantle metasomatism beneath the North Qaidam orogenic belt - Jinran Qiao; Chen-Ao Zhou; Jie Dong; Mark B. Allen; Liming Yang; Li Su; Shuguang Song (Lithos, 2023)

Systematic review of epidemiological studies evaluating the association between exposure to man-made vitreous fibers and non-malignant respiratory diseases - Natalie Suder Egnot; Hannah Allen; Rebecca Hazan; Mark F. Vater; Hristina Denic-Roberts; Renee LeClaire; Gary M. Marsh (Regulatory Toxicology and Pharmacology, 2023)

Tracing tectonic processes from Proto- to Paleo-Tethys in the East Kunlun Orogen by detrital zircons - Di Feng; Chao Wang; Shuguang Song; Lu Xiong; Guibin Zhang; Mark B. Allen; Jie Dong; Tao Wen; Li Su (Gondwana Research, 2023)

The effect of dietary carbohydrate to lipid ratios on growth performance in juvenile California yellowtail Seriola dorsalis - Jonas R. Miller; Guillaume P. Salze; Kevin R. Stuart; Mark A. Drawbridge; D. Allen Davis (Aquaculture, 2023)

Artificial aeration of an overloaded constructed wetland improves hypoxia but does not ameliorate high nitrogen loads - Danielle J. Allen; Mark Farrell; Jianyin Huang; Simon Plush; Luke M. Mosley (Journal of Environmental Management, 2023)

Detrital zircons from high-pressure trench sediments (Qilian Orogen): Constraints on continental-arc accretion, subduction initiation and polarity of the Proto-Tethys Ocean - Lu Xiong; Shuguang Song; Li Su; Guibin Zhang; Mark B. Allen; Di Feng; Shuwen Yang (Gondwana Research, 2023)

The effects of temperature extremes on survival in two semi‐arid Australian bird communities over three decades, with predictions to 2104 - Janet L. Gardner; Mark Clayton; Richard Allen; John Stein; Timothée Bonnet (Global Ecology and Biogeography, 2022)
Aim Organisms in arid and semi‐arid regions are frequently exposed to climatic extremes and accordingly among the most vulnerable to climate change. Studies of seasonal differences in vital rates, which mediate effects of climate on viability, are rare in arid species, limiting ability to project population trends. We quantified survival patterns for two bird communities as a function of exposure to temperature extremes in winter and summer, then projected survival patterns to 2104. Location Semi‐arid eastern Australia. Time period 1986–2016; 1986–2104. Major taxa studied Birds. Methods Using mark–recapture time‐dependent Cormack–Jolly–Seber models and data for 37 species from two >30‐year ringing programmes, we tested for effects on 6‐monthly survival of exposure to temperatures >38 and Results Survival probability declined strongly with increasing exposure to days >38°C and to a lesser extent to days Main conclusions We highlight the significance of temperature extremes for species' persistence in arid and semi‐arid regions, comprising 70% of Australia's landmass, and 40% globally. Our demography‐based results are consistent with physiological‐based projections evaluating avian survival in arid and semi‐arid regions globally and suggest rising summer temperatures pose a risk to population persistence in these regions.

An integrated approach to assessing abiotic and biotic threats to post‐fire plant species recovery: Lessons from the 2019–2020 Australian fire season - Rachael V. Gallagher; Stuart P. Allen; Berin D. E. Mackenzie; David A. Keith; Rachael H. Nolan; Libby Rumpff; Carl R. Gosper; Geoffrey Pegg; Stephen van Leeuwen; Mark K. J. Ooi; Colin J. Yates; Cory Merow; et al. (Global Ecology and Biogeography, 2022)
Aim Existing abiotic and biotic threats to plant species (e.g., disease, drought, invasive species) affect their capacity to recover post‐fire. We use a new, globally applicable framework to assess the vulnerability of 26,062 Australian plant species to a suite of active threats after the 2019–2020 fires. Location Australia. Time period 2019–2020. Major species studied Plants. Methods Spatial data for existing threats and information on species‐level susceptibility were combined with estimates of the extent of range burnt in southern Australia (> 22°S) to assign species against 10 criteria into vulnerability categories ( high , medium , low , none , data deficient ). We explore in detail results for three threats (drought, disease, feral animals), highlighting where impacts from multiple threats ranked high vulnerability may compound to reduce post‐fire recovery. Results Analysis of the full suite of 10 vulnerability criteria, which encompass a broad range of threats, revealed large numbers of species vulnerable to poor post‐fire recovery from one or more different hazards ( high vulnerability: 1,243 species; medium vulnerability: 2,450 species). Collectively, 457 plant species that burnt extensively (> 50%) across their range are highly vulnerable to poor recovery due to exposure to pre‐fire drought conditions (235 species), disease (186 species), or feral animals (97 species). Of these 457 species, 61 are vulnerable to more than one of these three threats, highlighting how a suite of interacting hazards can impact plant recovery after fire. Main conclusions While fire can renew plant populations by stimulating recruitment and resetting competitive interactions, the presence of existing threats in post‐fire landscapes jeopardizes recovery. The simultaneous impact of multiple threats that impact recovery can create a suite of hazards that contribute to declines and, potentially, extinction. Our method for rapid post‐fire vulnerability assessment can be applied to large numbers of plant species or other biota in fire affected regions globally.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Predicting Seabird Foraging Habitat for Conservation Planning in Atlantic Canada: Integrating Telemetry and Survey Data Across Thousands of Colonies - Robert A. Ronconi; David J. Lieske; Laura A. McFarlane Tranquilla; Sue Abbott; Karel A. Allard; Brad Allen; Amie L. Black; François Bolduc; Gail K. Davoren; Antony W. Diamond; David A. Fifield; Stefan Garthe; et al. (Frontiers in Marine Science, 2022)
Conservation of mobile organisms is difficult in the absence of detailed information about movement and habitat use. While the miniaturization of tracking devices has eased the collection of such information, it remains logistically and financially difficult to track a wide range of species across a large geographic scale. Predictive distribution models can be used to fill this gap by integrating both telemetry and census data to construct distribution maps and inform conservation goals and planning. We used tracking data from 520 individuals of 14 seabird species in Atlantic Canada to first compare foraging range and distance to shorelines among species across colonies, and then developed tree-based machine-learning models to predict foraging distributions for more than 5000 breeding sites distributed along more than 5000 km of shoreline. Despite large variability in foraging ranges among species, tracking data revealed clusters of species using similar foraging habitats (e.g., nearshore vs. offshore foragers), and within species, foraging range was highly colony-specific. Even with this variability, distance from the nesting colony was an important predictor of distribution for nearly all species, while distance from coastlines and bathymetry (slope and ruggedness) were additional important predictors for some species. Overall, we demonstrated the utility of tree-based machine-learning approach when modeling tracking data to predict distributions at un-sampled colonies. Although tracking and colony data have some shortcomings (e.g., fewer data for some species), where results need to be interpreted with care in some cases, applying methods for modeling breeding season distributions of seabirds allows for broader-scale conservation assessment. The modeled distributions can be used in decisions about planning for offshore recreation and commercial activities and to inform conservation planning at regional scales.

Observations of a species‐record deep dive by a central Pacific female scalloped hammerhead shark ( Sphyrna lewini ) - James M. Anderson; Patrick T. Rex; Kelsey Maloney; Mark Johnston; Deron Verbeck; Neil Allen; Kim Holland (Journal of Fish Biology, 2022)
A female scalloped hammerhead shark ( Sphyrna lewini ) conducted a species record deep dive to 1240 m in coastal‐pelagic waters off Hawaii Island. This extends the deepest known depth range of the species by over 200 m (650 ft) and highlights the question of the extent to which deep‐diving activity is mediated by physiological constraints, such as temperature and oxygen availability.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effects of regular cannabis and nicotine use on acute stress responses: chronic nicotine, but not cannabis use, is associated with blunted adrenocortical and cardiovascular responses to stress - Mustafa al’Absi; Briana DeAngelis; Mark Fiecas; Alan Budney; Sharon Allen (Psychopharmacology, 2022)

Adult Age Differences in Self-Reported Pain and Anterior CSF Space in Chiari Malformation - Maitane García; Maggie S. Eppelheimer; James R. Houston; Michelle L. Houston; Blaise Simplice Talla Nwotchouang; Kevin P. Kaut; Richard Labuda; J. Rajiv Bapuraj; Jahangir Maleki; Petra M. Klinge; Sarel Vorster; Mark G. Luciano; et al. (The Cerebellum, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

A National Status Report on United States Coral Reefs Based on 2012–2018 Data From National Oceanic and Atmospheric Administration’s National Coral Reef Monitoring Program - Erica K. Towle; E. Caroline Donovan; Heath Kelsey; Mary E. Allen; Hannah Barkley; Jeremiah Blondeau; Russell E. Brainard; Annie Carew; Courtney S. Couch; Maria K. Dillard; C. Mark Eakin; Kimberly Edwards; et al. (Frontiers in Marine Science, 2022)
National Oceanic and Atmospheric Administration’s Coral Reef Conservation Program supports the National Coral Reef Monitoring Program (NCRMP) in the United States Pacific, Atlantic, Caribbean, and Gulf of Mexico. NCRMP conducts standardized observations of biological, climatic, and socioeconomic indicators across American Samoa, Guam, the Main Hawaiian Islands, the Northwestern Hawaiian Islands, the Northern Mariana Islands, the Pacific Remote Islands, Florida, the Flower Garden Banks, Puerto Rico, and the United States Virgin Islands. NCRMP provides periodic, national-level assessments of the status of United States coral reef ecosystems and communities connected to them. In 2014, NCRMP partnered with the University of Maryland Center for Environmental Science on an unprecedented collaboration between federal and jurisdictional/state agencies, academia, and non-governmental organizations to synthesize NCRMP data into a reporting format designed to be accessible and relevant to the public and policy makers. The process involved multi-year data analyses of key benthic, fish, and climate indicators. In populated jurisdictions, socioeconomic data were integrated to assess public support for management actions, participation in pro-environmental behaviors, and awareness of threats to coral reefs. Jurisdictions were scored using a report-card scale (0–100%) by establishing references for each indicator using best-available historical data or expert opinion where historical data did not exist or were not statistically comparable. Despite overall ecosystem scores of Fair for all combined Atlantic (70%) and Pacific (74%) jurisdictions, the current trend is downward with a majority of United States coral reefs declining and vulnerable to further degradation. Remote, uninhabited reefs had an advantage with respect to reef fish population scores, i.e., Flower Garden Banks (85%) and Pacific Remote Islands (93%), when compared to populated location scores, i.e., Puerto Rico (63%) and Main Hawaiian Islands (66%). All coral reefs are highly impacted by climate change, and climate impacts were more pronounced than expected on remote reefs, i.e., the Northwestern Hawaiian Islands (58%). Presenting results in a report-card style facilitates communication to the public and policy makers, and provides a useful mechanism to garner support for management actions such as expanding protected areas; enforcing existing regulations; increasing climate change education; reducing land-based sources of pollution; and other actions to improve the trajectory of coral reef ecosystem conditions.

Impact of Surgical Status, Loneliness, and Disability on Interleukin 6, C-Reactive Protein, Cortisol, and Estrogen in Females with Symptomatic Type I Chiari Malformation - Monica A. Garcia; Xuan Li; Philip A. Allen; Douglas L. Delahanty; Maggie S. Eppelheimer; James R. Houston; Dawn M. Johnson; Frank Loth; Jahangir Maleki; Sarel Vorster; Mark G. Luciano (The Cerebellum, 2021)

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Conservation of Marine Foundation Species: Learning from Native Oyster Restoration from California to British Columbia - April D. Ridlon; Althea Marks; Chela J. Zabin; Danielle Zacherl; Brian Allen; Jeffrey Crooks; Gary Fleener; Edwin Grosholz; Betsy Peabody; Jodie Toft; Kerstin Wasson (Estuaries and Coasts, 2021)
Marine foundation species are critical to the structure and resilience of coastal ecosystems and provide key ecosystem services. Since many have suffered severe population declines, restoration of foundation species has been undertaken worldwide. The Olympia oyster ( Ostrea lurida ) is a foundation species, and the restoration of depleted populations is a priority for maintaining ecosystem function of estuaries along the west coast of North America. Here, we synthesize all native oyster restoration projects conducted from California, USA, to British Columbia, Canada, and analyze project goals, methods, and outcomes. Currently, restoration projects are spread unevenly across the species’ range, driven by locally varying goals and implemented with contrasting approaches. We highlight the value of regional strategic planning and decision support tools to evaluate project design and methods for restoration, including the selection of substrates and the targeted use of aquaculture. We recommend future investment in larger projects, which our analysis found were more cost-effective, but which have been relatively rare for this species. We also recommend that funders support monitoring over broader temporal and spatial scales than in the past to better characterize long-term effects of restoration on oyster populations and the services they provide beyond the project footprint. We found that most projects successfully supported native oysters and engaged local communities, and recommend similar efforts to continue to enhance understanding of Olympia oysters, which remain unfamiliar to many coastal residents. We believe that the results of this synthesis are broadly applicable to marine foundation species generally, and can inform restoration and conservation efforts worldwide.

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Mammal assemblage composition predicts global patterns in emerging infectious disease risk - Yingying X. G. Wang; Kevin D. Matson; Luca Santini; Piero Visconti; Jelle P. Hilbers; Mark A. J. Huijbregts; Yanjie Xu; Herbert H. T. Prins; Toph Allen; Zheng Y. X. Huang; Willem F. de Boer (Global Change Biology, 2021)
As a source of emerging infectious diseases, wildlife assemblages (and related spatial patterns) must be quantitatively assessed to help identify high‐risk locations. Previous assessments have largely focussed on the distributions of individual species; however, transmission dynamics are expected to depend on assemblage composition. Moreover, disease–diversity relationships have mainly been studied in the context of species loss, but assemblage composition and disease risk (e.g. infection prevalence in wildlife assemblages) can change without extinction. Based on the predicted distributions and abundances of 4466 mammal species, we estimated global patterns of disease risk through the calculation of the community‐level basic reproductive ratio R0, an index of invasion potential, persistence, and maximum prevalence of a pathogen in a wildlife assemblage. For density‐dependent diseases, we found that, in addition to tropical areas which are commonly viewed as infectious disease hotspots, northern temperate latitudes included high‐risk areas. We also forecasted the effects of climate change and habitat loss from 2015 to 2035. Over this period, many local assemblages showed no net loss of species richness, but the assemblage composition (i.e. the mix of species and their abundances) changed considerably. Simultaneously, most areas experienced a decreased risk of density‐dependent diseases but an increased risk of frequency‐dependent diseases. We further explored the factors driving these changes in disease risk. Our results suggest that biodiversity and changes therein jointly influence disease risk. Understanding these changes and their drivers and ultimately identifying emerging infectious disease hotspots can help health officials prioritize resource distribution.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

Expert opinion on American common eiders in eastern North America: international information needs for future conservation - Kristen Noel; Nic McLellan; Scott Gilliland; Karel A. Allard; Brad Allen; Shawn Craik; Anaïs Demagny; Matthew D. English; Antony Diamond; Jean-François Giroux; Alan Hanson; H. W. Heusmann; et al. (Socio-Ecological Practice Research, 2021)

A Global Ecological Classification of Coastal Segment Units to Complement Marine Biodiversity Observation Network Assessments - Roger Sayre; Kevin Butler; Keith Van Graafeiland; Sean Breyer; Dawn Wright; Charlie Frye; Deniz Karagulle; Madeline Martin; Jill Cress; Tom Allen; Rebecca Allee; Rost Parsons; et al. (Oceanography, 2021)
A new data layer provides Coastal and Marine Ecological Classification Standard (CMECS) labels for global coastal segments at 1 km or shorter resolution. These characteristics are summarized for six US Marine Biodiversity Observation Network (MBON) sites and one MBON Pole to Pole of the Americas site in Argentina. The global coastlines CMECS classifications were produced from a partitioning of a 30 m Landsat-derived shoreline vector that was segmented into 4 million 1 km or shorter segments. Each segment was attributed with values from 10 variables that represent the ecological settings in which the coastline occurs, including properties of the adjacent water, adjacent land, and coastline itself. The 4 million segments were classified into 81,000 coastal segment units (CSUs) as unique combinations of variable classes. We summarize the process to develop the CSUs and derive summary descriptions for the seven MBON case study sites. We discuss the intended application of the new CSU data for research and management in coastal areas.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Landslides of the 1920 Haiyuan earthquake, northern China - Yueren Xu; Jing Liu-Zeng; Mark B. Allen; Weiheng Zhang; Peng Du (Landslides, 2021)

Groundwater recharge to a structurally complex aquifer system on the island of Tobago (Republic of Trinidad and Tobago) - David F. Boutt; Marsha Allen; Mark Settembrino; Amber Bonarigo; Joseph Ingari; Rose Demars; Lee Ann Munk (Hydrogeology Journal, 2021)

HPV and HPV Vaccination Knowledge and Attitudes Among Medical Students in Alabama - Casey L. Daniel; Lane McLendon; Chelsea L. Green; Katie J. Anderson; Jennifer Y. Pierce; Allen Perkins; Mark Beasley (Journal of Cancer Education, 2021)

Nickel ferrite nanoenabled graphene oxide (NiFe2O4@GO) as photoactive nanocomposites for water treatment - Allen Rhay B. Bayantong; Yu-Jen Shih; Cheng-Di Dong; Sergi Garcia-Segura; Mark Daniel G. de Luna (Environmental Science and Pollution Research, 2021)

Compromised resting cerebral metabolism after sport-related concussion: A calibrated MRI study - Allen A. Champagne; Nicole S. Coverdale; Juan Fernandez-Ruiz; Clarisse I. Mark; Douglas J. Cook (Brain Imaging and Behavior, 2021)

Acute rewarding and disinhibiting effects of alcohol as indicators of drinking habits - Holley C. Allen; Jessica Weafer; Michael J. Wesley; Mark T. Fillmore (Psychopharmacology, 2021)

Co-localized impaired regional cerebrovascular reactivity in chronic concussion is associated with BOLD activation differences during a working memory task - Nicole S. Coverdale; Juan Fernandez-Ruiz; Allen A. Champagne; Clarisse I. Mark; Douglas J. Cook (Brain Imaging and Behavior, 2020)

The interaction of physical and biological factors drives phytoplankton spatial distribution in the northern California Current - Jeffrey W. Krause; Mark A. Brzezinski; John L. Largier; Heather M. McNair; Michael Maniscalco; Kay D. Bidle; Andrew E. Allen; Kimberlee Thamatrakoln (Limnology and Oceanography, 2020)
Transitions in phytoplankton community composition are typically attributed to ecological succession even in physically dynamic upwelling systems like the California Current Ecosystem (CCE). An expected succession from a high‐chlorophyll (~ 10 μ g L −1 ) diatom‐dominated assemblage to a low‐chlorophyll ( μ g L −1 ) non‐diatom dominated assemblage was observed during a 2013 summer upwelling event in the CCE. Using an interdisciplinary field‐based space‐for‐time approach leveraging both biogeochemical rate measurements and metatranscriptomics, we suggest that this successional pattern was driven primarily by physical processes. An annually recurring mesoscale eddy‐like feature transported significant quantities of high‐phytoplankton‐biomass coastal water offshore. Chlorophyll was diluted during transport, but diatom contributions to phytoplankton biomass and activity (49–62% observed) did not decline to the extent predicted by dilution (18–24% predicted). Under the space‐for‐time assumption, these trends infer diatom biomass and activity and were stimulated during transport. This is hypothesized to result from decreased contact rates with mortality agents (e.g., viruses) and release from nutrient limitation (confirmed by rate data nearshore), as predicted by the Disturbance‐Recovery hypothesis of phytoplankton bloom formation. Thus, the end point taxonomic composition and activity of the phytoplankton assemblage being transported by the eddy‐like feature were driven by physical processes (mixing) affecting physiological (release from nutrient limitation, increased growth) and ecological (reduced mortality) factors that favored the persistence of the nearshore diatoms during transit. The observed connection between high‐diatom‐biomass coastal waters and non‐diatom‐dominated offshore waters supports the proposed mechanisms for this recurring eddy‐like feature moving seed populations of coastal phytoplankton offshore and thereby sustaining their activity.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Using different body size measures can lead to different conclusions about the effects of climate change - Liam D. Bailey; Loeske E. B. Kruuk; Richard Allen; Mark Clayton; John Stein; Janet L. Gardner (Journal of Biogeography, 2020)
Aim Declining animal body size has been proposed as a general response to increasing global temperatures that should be observed across a broad biogeographical scale. However, published studies have shown large variation in both the magnitude and direction of body size trends. We aim to investigate how the way body size is measured (body mass, structural size, body condition) may contribute to differences in body size trends between studies. Location Semi‐arid Australia. Taxon White‐plumed honeyeater ( Ptilotula penicillatus ). Methods We studied two separate populations of P. penicillatus over 30 years to investigate the associations between weather and body size. We first investigated how body mass has been affected by weather conditions at each site and then determined how these same local weather conditions affected the constituent components of body mass (structural size and body condition). Results The magnitude and direction of weather effects differed with the measure of body size used. Average structural size (wing length) increased with increasing temperatures while average body condition decreased. As body mass is a composite of structural size and body condition, the magnitude and direction of body mass trends was affected by trends in these two other traits. For example, differences in temperature effects on structural size between our two sites led to clear differences in body mass trends. Main Conclusions Trends in body size will be strongly affected by the choice of body size measure used in analyses. Change in body mass can be particularly difficult to interpret as it will be a composite of changes in both structural size and body condition. Our results indicate that it is difficult to compare studies using different measures of body size. Using consistent measures of body size will be important to better understand the general effects of climate change on body size.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Evaluating flood resilience in rural communities: a case-based assessment of Dyer County, Tennessee - Madeline Allen; Leslie Gillespie-Marthaler; Mark Abkowitz; Janey Camp (Natural Hazards, 2020)

Combining sediment fingerprinting with age-dating sediment using fallout radionuclides for an agricultural stream, Walnut Creek, Iowa, USA - Allen C. Gellis; Christopher C. Fuller; Peter Van Metre; Christopher T. Filstrup; Mark D. Tomer; Kevin J. Cole; Timur Y. Sabitov (Journal of Soils and Sediments, 2019)

Uncertainty in geomorphological responses to climate change - Stephan Harrison; Tim Mighall; David A. Stainforth; Philip Allen; Mark Macklin; Edward Anderson; Jasper Knight; Dmitri Mauquoy; David Passmore; Brice Rea; Matteo Spagnolo; Sarah Shannon (Climatic Change, 2019)

A tropical Australian refuge for photosymbiotic benthic fauna - Zoe T. Richards; Rodrigo Garcia; Glenn Moore; Jane Fromont; Lisa Kirkendale; Monika Bryce; Clay Bryce; Ana Hara; Jenelle Ritchie; Oliver Gomez; Corey Whisson; Mark Allen; et al. (Coral Reefs, 2019)

Feather mercury concentrations in North American raptors sampled at migration monitoring stations - Ryan P. Bourbour; Breanna L. Martinico; Joshua T. Ackerman; Mark P. Herzog; Angus C. Hull; Allen M. Fish; Joshua M. Hull (Ecotoxicology, 2019)

Bacteria and viruses in the nasopharynx immediately prior to onset of acute lower respiratory infections in Indigenous Australian children - Heidi C. Smith-Vaughan; Michael J. Binks; Jemima Beissbarth; Anne B. Chang; Gabrielle B. McCallum; Ian M. Mackay; Peter S. Morris; Robyn L. Marsh; Paul J. Torzillo; Danielle F. Wurzel; Keith Grimwood; Elizabeth Nosworthy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

An Electrophysiological Study of Cognitive and Emotion Processing in Type I Chiari Malformation - James R. Houston; Michelle L. Hughes; Mei-Ching Lien; Bryn A. Martin; Francis Loth; Mark G. Luciano; Sarel Vorster; Philip A. Allen (The Cerebellum, 2018)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Turbulence in the presence of internal waves in the bottom boundary layer of the California inner shelf - Rachel M. Allen; Julian A. Simeonov; Joseph Calantoni; Mark T. Stacey; Evan A. Variano (Ocean Dynamics, 2018)

Multi-Century Record of Anthropogenic Impacts on an Urbanized Mesotidal Estuary: Salem Sound, MA - J. Bradford Hubeny; Ellen Kristiansen; Andrew Danikas; Jun Zhu; Francine M. G. McCarthy; Mark G. Cantwell; Barbara Warren; Douglas Allen (Estuaries and Coasts, 2018)

Starting a Medical Technology Venture as a Young Academic Innovator or Student Entrepreneur - Amir Manbachi; Katlin Kreamer-Tonin; Philipp Walch; Nao J. Gamo; Parastoo Khoshakhlagh; Yu Shrike Zhang; Charles Montague; Soumyadipta Acharya; Elizabeth A. Logsdon; Robert H. Allen; Nicholas J. Durr; Mark G. Luciano; et al. (Annals of Biomedical Engineering, 2018)

Controlled Ion Release from Novel Polyester/Ceramic Composites Enhances Osteoinductivity - Soheila Ali Akbari Ghavimi; Rama Rao Tata; Andrew J. Greenwald; Brittany N. Allen; David A. Grant; Sheila A. Grant; Mark W. Lee; Bret D. Ulery (The AAPS Journal, 2017)

Virus occurrence in private and public wells in a fractured dolostone aquifer in Canada - Amy S. Allen; Mark A. Borchardt; Burney A. Kieke; Kari E. Dunfield; Beth L. Parker (Hydrogeology Journal, 2017)

First-in-human studies of seletalisib, an orally bioavailable small-molecule PI3Kδ inhibitor for the treatment of immune and inflammatory diseases - Eric Helmer; Mark Watling; Emma Jones; Dominique Tytgat; Mark Jones; Rodger Allen; Andrew Payne; Annelize Koch; Eugene Healy (European Journal of Clinical Pharmacology, 2017)

Effort rights‐based management - Dale Squires; Mark Maunder; Robin Allen; Peder Andersen; Kepa Astorkiza; Douglas Butterworth; Gonzalo Caballero; Raymond Clarke; Hans Ellefsen; Patrice Guillotreau; John Hampton; Rögnvaldur Hannesson; et al. (Fish and Fisheries, 2017)
Effort rights‐based fisheries management ( RBM ) is less widely used than catch rights, whether for groups or individuals. Because RBM on catch or effort necessarily requires a total allowable catch ( TAC ) or total allowable effort ( TAE ), RBM is discussed in conjunction with issues in assessing fish populations and providing TAC s or TAE s. Both approaches have advantages and disadvantages, and there are trade‐offs between the two approaches. In a narrow economic sense, catch rights are superior because of the type of incentives created, but once the costs of research to improve stock assessments and the associated risks of determining the TAC and costs of monitoring, control, surveillance and enforcement are taken into consideration, the choice between catch or effort RBM becomes more complex and less clear. The results will be case specific. Hybrid systems based on both catch and effort are increasingly employed to manage marine fisheries to capture the advantages of both approaches. In hybrid systems, catch or effort RBM dominates and controls on the other supplements. RBM using either catch or effort by itself addresses only the target species stock externality and not the remaining externalities associated with by‐catch and the ecosystem.

Survival probabilities and movements of harbor seals in central California - Suzanne C. Manugian; Denise Greig; Derek Lee; Benjamin H. Becker; Sarah Allen; Mark S. Lowry; James T. Harvey (Marine Mammal Science, 2017)
Harbor seal numbers and population trajectories differ by location in central California. Within San Francisco Bay ( SFB ) counts have been relatively stable since the 1972 Marine Mammal Protection Act, but in coastal areas like Tomales Bay ( TB ), counts increased before stabilizing in the 1990s. Emigration, poor survival, and environmental effects have been hypothesized as contributors to differences between trajectories; however, basic demographic data were not available to evaluate these hypotheses. We monitored 32 radio‐tagged adult females ( SFB n = 17, TB n = 15) for 20 mo (2011–2013), and estimated survival, resight, and movement probabilities using mark‐resight analyses and multistate mark‐resight models. Annual survival probability for both sites was 0.90 (95% CI = 0.18–0.99). Six seals were observed moving between locations resulting in an estimated probability of 0.042 (95% CI = 0.023–0.076) per month equal movement between sites. Resight probability was less in SFB relative to TB , likely due to differential haul‐out access, area surveyed, visibility, and resight effort. Because of wide confidence intervals and low precision of these first estimates of adult female harbor seal survival in California, this demographic must be further examined to dismiss its contribution to differing population trajectories. Using aerial survey data, we estimated 950 harbor seals in SFB (95% CI = 715–1,184) confirming numbers are still stable.

The importance of motivation, weapons, and foul odors in driving encounter competition in carnivores - Maximilian L. Allen; Christopher C. Wilmers; L. Mark Elbroch; Julie M. Golla; Heiko U. Wittmer (Ecology, 2016)
Encounter competition is interference competition in which animals directly contend for resources. Ecological theory predicts the trait that determines the resource holding potential ( RHP ), and hence the winner of encounter competition, is most often body size or mass. The difficulties of observing encounter competition in complex organisms in natural environments, however, has limited opportunities to test this theory across diverse species. We studied the outcome of encounter competition contests among mesocarnivores at deer carcasses in California to determine the most important variables for winning these contests. We found some support for current theory in that body mass is important in determining the winner of encounter competition, but we found that other factors including hunger and species‐specific traits were also important. In particular, our top models were “strength and hunger” and “size and hunger,” with models emphasizing the complexity of variables influencing outcomes of encounter competition. In addition, our wins above predicted ( WAP ) statistic suggests that an important aspect that determines the winner of encounter competition is species‐specific advantages that increase their RHP , as bobcats ( Lynx rufus ) and spotted skunks ( Spilogale gracilis ) won more often than predicted based on mass. In complex organisms, such as mesocarnivores, species‐specific adaptations, including strategic behaviors, aggressiveness, and weapons, contribute to competitive advantages and may allow certain species to take control or defend resources better than others. Our results help explain how interspecific competition shapes the occurrence patterns of species in ecological communities.

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Reduction of Ethanol Yield from Switchgrass Infected with Rust Caused by Puccinia emaculata - Virginia R. Sykes; Fred L. Allen; Jonathan R. Mielenz; C. Neal Stewart; Mark T. Windham; Choo Y. Hamilton; Miguel Rodriguez; Kelsey L. Yee (BioEnergy Research, 2016)

Acoustical deterrence of Silver Carp (Hypophthalmichthys molitrix) - Brooke J. Vetter; Aaron R. Cupp; Kim T. Fredricks; Mark P. Gaikowski; Allen F. Mensinger (Biological Invasions, 2015)

Temperature and the biogeography of algal stoichiometry - Gabriel Yvon‐Durocher; Matteo Dossena; Mark Trimmer; Guy Woodward; Andrew P. Allen (Global Ecology and Biogeography, 2015)
Aim The average carbon‐to‐nitrogen‐to‐phosphorus ratio (C:N:P) of marine algae is known to be tightly coupled to that of the inorganic pools of C , N and P in the ocean interior (i.e. the Redfield ratio), and therefore plays a key role in regulating the C and N cycles in the ocean. The C:N:P ratio of algae also varies substantially, both within and among taxa, in response to variation in the abiotic environment, raising the possibility that biogeochemical controls on the marine C and N cycles may shift as a result of climate change. However, the role of temperature in driving phenotypic variation in stoichiometry within algal taxa, as well as biogeographic variation in particulate C , N and P among oceanic regions, remains largely unresolved. Location Global. Methods To assess the extent to which temperature controls algal stoichiometry we performed two complementary meta‐analyses. First, we characterized the global temperature dependence of algal stoichiometry by analysing field data that encompassed 767 estimates of C : N : P from 22 oceanic sites spanning over 130° of latitude. Second, we characterized the within‐species acclimation responses of C : N : P stoichiometry to temperature by analysing data that encompassed 17 experiments, 9 species and 4 taxonomic classes. Results The geographic analyses demonstrated that the N : P and C : P ratios of marine algae were best predicted by latitudinal variation in average sea‐surface temperature, and that both ratios increased 2.6‐fold from 0 to 30 ° C . These global‐scale temperature responses, which largely reflect geographic variation in the species compositions of algal assemblages, were of similar magnitude to the average within‐species response of the N : P and C : P ratios to experimental temperature manipulations. Main conclusions The congruence between field and experimental observations suggests that temperature‐dependent physiological mechanisms operating at the subcellular level play an important role in determining the stoichiometry of algae in the world's oceans.

Effects of flow regime on growth rate in freshwater drum, Aplodinotus grunniens - Stephen J. Jacquemin; Jason C. Doll; Mark Pyron; Michael Allen; Dustin A. S. Owen (Environmental Biology of Fishes, 2015)

Pleistocene diversification of the Pomacentrus coelestis species complex (Pisces: Pomacentridae): historical biogeography and species boundaries - Laurie Sorenson; Gerald R. Allen; Mark V. Erdmann; Chang-Feng Dai; Shang-Yin Vanson Liu (Marine Biology, 2014)

Mosaic partial deletion of the PTEN gene in a patient with Cowden syndrome - Erin E. Salo-Mullen; Jinru Shia; Isaac Brownell; Peter Allen; Monica Girotra; Mark E. Robson; Kenneth Offit; Jose G. Guillem; Arnold J. Markowitz; Zsofia K. Stadler (Familial Cancer, 2014)

Long-term behavior at foraging sites of adult female loggerhead sea turtles (Caretta caretta) from three Florida rookeries - Allen M. Foley; Barbara A. Schroeder; Robert Hardy; Sandra L. MacPherson; Mark Nicholas (Marine Biology, 2014)

Fin tissues as surrogates of white muscle when assessing carbon and nitrogen stable isotope levels for Arctic and brook char - R. Allen Curry; Mark D. Gautreau; Joseph M. Culp (Environmental Biology of Fishes, 2014)

A dynamic model of the cellular carbon to chlorophyll ratio applied to a batch culture and a continental shelf ecosystem - Mark E. Baird; Peter J. Ralph; Farhan Rizwi; Karen Wild-Allen; Andrew D. L. Steven (Limnology and Oceanography, 2013)
A novel parameterization of the dynamical relationship between cellular carbon (C) and chlorophyll (Chl) is developed using a Chl synthesis term that includes the physiological status of the cell and the effect of packaging of pigments within cells. The geometric derivation highlights the non‐linear relationship between Chl content and absorption due to the package effect. When parameterized for a generic 3 µm radius phytoplankton cell, the model reproduces the magnitude and daily variations of C : Chl and C : nitrogen ratios of the diatom Skeletonema costatum in published laboratory experiments. The parameterization is then applied in a three‐dimensional biogeochemical model containing three phytoplankton classes in the coastal waters off southeast Tasmania, Australia, which demonstrates the behavior of the dynamic Chl parameterization over a range of light‐ and nutrient‐limiting environments for phytoplankton of different sizes and growth rates. The model produces C : Chl ratios of ∼ 12–20 (weight : weight) and ∼ 60–80 for phytoplankton communities dominated by fast‐growing small and fast‐growing large cells, respectively, close to the ratios of 17 and 76 observed at two sampling stations during periods with diatom‐ and flagellate‐dominated communities. Throughout the simulation, community C : Chl ratios generally vary between 12 and 200, which is similar to the range observed globally. In the new parameterization, C : Chl ratios are most influenced by the package effect for light‐limited, slow‐growing large microalgae, with physiological processes becoming important for smaller, nutrient‐limited, fast‐growing microalgae.

Stochastic and deterministic drivers of spatial and temporal turnover in breeding bird communities - James C. Stegen; Amy L. Freestone; Thomas O. Crist; Marti J. Anderson; Jonathan M. Chase; Liza S. Comita; Howard V. Cornell; Kendi F. Davies; Susan P. Harrison; Allen H. Hurlbert; Brian D. Inouye; Nathan J. B. Kraft; et al. (Global Ecology and Biogeography, 2013)
Aim A long‐standing challenge in ecology is to identify the suite of factors that lead to turnover in species composition in both space and time. These factors might be stochastic (e.g. sampling and priority effects) or deterministic (e.g. competition and environmental filtering). While numerous studies have examined the relationship between turnover and individual drivers of interest (e.g. primary productivity, habitat heterogeneity, or regional – ‘gamma’ – diversity), few studies have disentangled the simultaneous influences of multiple stochastic and deterministic processes on both temporal and spatial turnover. If turnover is governed primarily by stochastic sampling processes, removing the sampling effects of gamma diversity should result in non‐significant relationships between turnover and environmental variables. Conversely, if deterministic processes govern turnover patterns, removing sampling effects will have little influence on turnover gradients. Here, we test these predictions. Location The United States. Methods Continental‐scale, multidecadal data were used to quantify spatial and temporal turnover in avian community composition within 295 survey routes. A series of regression and structural equation models were coupled with a null model to construct statistical models describing turnover patterns. Results Examining explanatory variables alone or in combination showed that spatial and temporal turnover increased together, decreased with primary productivity and increased with habitat heterogeneity. The relationships between turnover and all variables became weaker when sampling effects were removed, but relationships with primary productivity and habitat heterogeneity remained relatively strong. In addition, spatial turnover increased strongly with spatial gamma diversity after sampling effects were removed. Main conclusions Our results show that spatial and temporal turnover are related to each other through a stochastic sampling process, but that each type of turnover is further influenced by deterministic processes. The relative influence of deterministic processes appears, however, to decrease with primary productivity and increase with habitat heterogeneity across an east–west longitudinal gradient in North America.

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Global Competency and Issues in Contemporary Education / Agroforestry - Susan Moore; Erin Sills; Lee Allen; Douglas Frederick; Frederick Cubbage; John Garland; Julie Lydick; Gordon Holley; Jodi Roberts; Stephen Grado; Zhu Ning; Shannon Fowler; et al. (Journal of Forestry, 2011)
34We performed a five year integrated research, extension and education project aimed at strengthening global competence of students and faculty through collaboration in forestry. We sought to improve our students' ability to cooperate, increase their understanding of global dynamics of forestry markets and enhance their knowledge of various approaches to forest management and conservation with Chile as the focus. The project had four key components: (1) facilitate faculty and student involvement in Chile through Spanish language training, a website, and visits by Chilean faculty; (2) support NC State faculty and student research and study in Chile through travel grants and study tours; (3) build on faculty sabbaticals in Chile by funding student research assistants; and (4) disseminate information from Chile through multiple channels to both the university and professional communities. The faculty exchange visits; graduate student research; and participation of NCSU students, faculty and staff in the study tours to Chile had substantial effects when the participants returned to the US and disseminated information about their experiences through both formal and informal mechanisms. Both students and faculty at NCSU are more aware of forestry research, policy and management in Chile. Faculty at NCSU and Chilean universities Universidad de Concepción and Universidad de Austral have established a strong basis for collaboration and are continuing to work together on funding proposals, research, and papers. Students who participated in the study tours learned about both the culture and forestry in Chile, including similarities, differences, and lessons for the US. This presentation will describe the activities, outcomes and ongoing impacts of the project.

In silico genomic subtraction guides development of highly accurate, DNA-based diagnostics for Ralstonia solanacearum race 3 biovar 2 and blood disease bacterium - Ryo Kubota; Mark A. Schell; Gabriel D. Peckham; Joanne Rue; Anne M. Alvarez; Caitilyn Allen; Daniel M. Jenkins (Journal of General Plant Pathology, 2011)

Parasites of European hedgehogs (Erinaceus europaeus) in Britain: epidemiological study and coprological test evaluation - Gabriella Gaglio; Simon Allen; Lee Bowden; Mark Bryant; Eric R. Morgan (European Journal of Wildlife Research, 2010)

Pathogenesis of Pulmonary Cryptococcus gattii Infection: A Rat Model - Mark B. Krockenberger; Richard Malik; Popchai Ngamskulrungroj; Luciana Trilles; Patricia Escandon; Susan Dowd; Chris Allen; Uwe Himmelreich; Paul J. Canfield; Tania C. Sorrell; Wieland Meyer (Mycopathologia, 2010)

Does socioeconomic disparity in cancer incidence vary across racial/ethnic groups? - Daixin Yin; Cyllene Morris; Mark Allen; Rosemary Cress; Janet Bates; Lihua Liu (Cancer Causes & Control, 2010)

Using logistic regression models to predict breeding success in male Adélie penguins (Pygoscelis adeliae) - Emma J. Marks; Allen G. Rodrigo; Dianne H. Brunton (Polar Biology, 2010)

Analyzing complex traits with congenic strains - Haifeng Shao; David S. Sinasac; Lindsay C. Burrage; Craig A. Hodges; Pamela J. Supelak; Mark R. Palmert; Carol Moreno; Allen W. Cowley; Howard J. Jacob; Joseph H. Nadeau (Mammalian Genome, 2010)

Risk of cancer among rheumatoid arthritis patients in California - Arti Parikh-Patel; Richard H. White; Mark Allen; Rosemary Cress (Cancer Causes & Control, 2009)

Island biogeography of Caribbean coral reef fish - Stuart A. Sandin; Mark J. A. Vermeij; Allen H. Hurlbert (Global Ecology and Biogeography, 2008)
Aim The goal of our study was to test fundamental predictions of biogeographical theories in tropical reef fish assemblages, in particular relationships between fish species richness and island area, isolation and oceanographic variables (temperature and productivity) in the insular Caribbean. These analyses complement an analogous and more voluminous body of work from the tropical Indo‐Pacific. The Caribbean is more limited in area with smaller inter‐island distances than the Indo‐Pacific, providing a unique context to consider fundamental processes likely to affect richness patterns of reef fish. Location Caribbean Sea. Methods We compiled a set of data describing reef‐associated fish assemblages from 24 island nations across the Caribbean Sea, representing a wide range of isolation and varying in land area from 53 to 110,860 km 2 . Regression‐based analyses compared the univariate and combined effects of island‐specific physical predictors on fish species richness. Results We found that diversity of reef‐associated fishes increases strongly with increasing island area and with decreasing isolation. Richness also increases with increasing nearshore productivity. Analyses of various subsets of the entire data set reveal the robustness of the richness data and biogeographical patterns. Main conclusions Within the relatively small and densely packed Caribbean basin, fish species richness fits the classical species–area relationship. Richness also was related negatively to isolation, suggesting direct effects of dispersal limitation in community assembly. Because oceanic productivity was correlated with isolation, however, the related effects of system‐wide productivity on richness cannot be disentangled. These results highlight fundamental mechanisms that underlie spatial patterns of biodiversity among Caribbean coral reefs, and which are probably also are functioning in the more widespread and heterogeneous reefs of the Indo‐Pacific.

Cancer risk in a cohort of patients with systemic lupus erythematosus (SLE) in California - Arti Parikh-Patel; Richard H. White; Mark Allen; Rosemary Cress (Cancer Causes & Control, 2008)

Utilising high throughput technologies for the determination of the reaction network of the l-proline catalysed aldol reaction - Katarina Novakovic; Mark J. Willis; Allen R. Wright (Clean Technologies and Environmental Policy, 2008)

Rhizobacterial volatile emissions regulate auxin homeostasis and cell expansion in Arabidopsis - Huiming Zhang; Mi-Seong Kim; Venkat Krishnamachari; Paxton Payton; Yan Sun; Mark Grimson; Mohamed A. Farag; Choong-Min Ryu; Randy Allen; Itamar S. Melo; Paul W. Paré (Planta, 2007)

El Niño periods increase growth of juvenile white seabass (Atractoscion nobilis) in the Southern California Bight - Jonathan P. Williams; Larry G. Allen; Mark A. Steele; Daniel J. Pondella (Marine Biology, 2007)

RAPID: Research on Automated Plankton Identification - Mark Benfield; Philippe Grosjean; Phil Culverhouse; Xabier Irigolen; Michael Sieracki; Angel Lopez-Urrutia; Hans Dam; Qiao Hu; Cabell Davis; Allen Hanson; Cynthia Pilskaln; Edward Riseman; et al. (Oceanography, 2007)

Evolution and the latitudinal diversity gradient: speciation, extinction and biogeography - Gary G. Mittelbach; Douglas W. Schemske; Howard V. Cornell; Andrew P. Allen; Jonathan M. Brown; Mark B. Bush; Susan P. Harrison; Allen H. Hurlbert; Nancy Knowlton; Harilaos A. Lessios; Christy M. McCain; Amy R. McCune; et al. (Ecology Letters, 2007)
A latitudinal gradient in biodiversity has existed since before the time of the dinosaurs, yet how and why this gradient arose remains unresolved. Here we review two major hypotheses for the origin of the latitudinal diversity gradient. The time and area hypothesis holds that tropical climates are older and historically larger, allowing more opportunity for diversification. This hypothesis is supported by observations that temperate taxa are often younger than, and nested within, tropical taxa, and that diversity is positively correlated with the age and area of geographical regions. The diversification rate hypothesis holds that tropical regions diversify faster due to higher rates of speciation (caused by increased opportunities for the evolution of reproductive isolation, or faster molecular evolution, or the increased importance of biotic interactions), or due to lower extinction rates. There is phylogenetic evidence for higher rates of diversification in tropical clades, and palaeontological data demonstrate higher rates of origination for tropical taxa, but mixed evidence for latitudinal differences in extinction rates. Studies of latitudinal variation in incipient speciation also suggest faster speciation in the tropics. Distinguishing the roles of history, speciation and extinction in the origin of the latitudinal gradient represents a major challenge to future research.

A genetic test for recruitment enhancement in Chesapeake Bay oysters, Crassostrea virginica, after population supplementation with a disease tolerant strain - Matthew P. Hare; Standish K. Allen; Paulette Bloomer; Mark D. Camara; Ryan B. Carnegie; Jenna Murfree; Mark Luckenbach; Donald Meritt; Cheryl Morrison; Kennedy Paynter; Kimberly S. Reece; Colin G. Rose (Conservation Genetics, 2006)

Polymer Microneedles for Controlled-Release Drug Delivery - Jung-Hwan Park; Mark G. Allen; Mark R. Prausnitz (Pharmaceutical Research, 2006)

Structural analysis of a designed inhibitor complexed with the hemagglutinin-neuraminidase of Newcastle disease virus - Charlotte Ryan; Viateslav Zaitsev; David J. Tindal; Jeffrey C. Dyason; Robin J. Thomson; Irina Alymova; Allen Portner; Mark von Itzstein; Garry Taylor (Glycoconjugate Journal, 2006)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

The emerging field of closed ecological systems - John P. Allen; Mark Nelson (Journal of Biogeography, 2005)

Cytokine gene polymorphisms in ischaemic heart disease: investigation using family-based tests of association - Paul G. McGlinchey; Mark S. Spence; Chris C. Patterson; Adrian R. Allen; Gillian Murphy; David A. Savage; A. Peter Maxwell; Pascal P. McKeown (Journal of Molecular Medicine, 2004)

Dynamics of silicon metabolism and silicon isotopic discrimination in a marine diatomas a function of pCO 2 - Allen J. Milligan; Diana E. Varela; Mark A. Brzezinski; François M. M. Morel (Limnology and Oceanography, 2004)
Opal accumulation rates in sediments have been used as a proxy for carbon flux, but there is poor understanding of the factors that regulate the Si quota of diatoms. Natural variation in silicon isotopes (δ 30 Si) in diatom frustules recovered from sediment cores are an alternative to opal mass for reconstructing diatom Si use and potential C export over geological timescales. Understanding the physiological factors that may influence the Si quota and the δ 30 Si isotopic signal is vital for interpreting biogenic silica as a paleoproxy. We investigated the influence of p CO 2 on the Si quota, fluxes across the cell membrane, and frustule dissolution in the marine diatom Thalassiosira weissflogii and determined the effect that p CO 2 has on the isotopic fractionation of Si. We found that our Si flux estimates mass balance and, for the first time, describe the Si budget of a diatom. The Si quota rose in cells grown with low p CO 2 (100 ppm) compared with controls (370 ppm), and the increased quota was the result of greater retention of Si (i.e., lower losses of Si through efflux and dissolution). The ratio of efflux : influx decreased twofold as p CO 2 decreased from 750 to 100 ppm. The efflux of silicon is shown to significantly bias measurements of silica dissolution rates determined by isotope dilution, but no effect on the Si isotopic enrichment factor (ε) was observed. The latter effect suggests that silicon isotopic discrimination in diatoms is set by the Si transport step rather than by the polymerization step. This observation supports the use of the v signal of biogenic silica as an indicator of the percentage utilization of silicic acid.

Metal binding to cowpea chlorotic mottle virus using terbium(III) fluorescence - Gautam Basu; Mark Allen; Deborah Willits; Mark Young; Trevor Douglas (JBIC Journal of Biological Inorganic Chemistry, 2003)

High breast cancer incidence rates among California teachers: results from the California Teachers Study (United States) - Leslie Bernstein; Mark Allen; Hoda Anton-Culver; Dennis Deapen; Pamela L. Horn-Ross; David Peel; Richard Pinder; Peggy Reynolds; Jane Sullivan-Halley; Dee West; William Wright; Al Ziogas; et al. (Cancer Causes & Control, 2002)

The DNA-binding ability of HIVEP3/KRC decreases upon activation of V(D)J recombination - Lai-Chu Wu; Mark D. Hicar; Joung-woo Hong; Carl E. Allen (Immunogenetics, 2001)

Nutrient Supply and Fertilization Efficiency in Midrotation Loblolly Pine Plantations: A Modeling Analysis - Mark Ducey; H. Lee Allen (Forest Science, 2001)
We simulated the 10 yr macronutrient budgets for 14 installations in a regionwide midrotation loblolly pine (Pinus taeda L.) fertilization study using NUTREM, a simplified model of carbon and nutrient uptake and distribution. Each installation includes 2–4 replications of N and P addition in a two-way factorial design. By approximating the constraints on nutrient use as elements in a linear programming problem, and estimating the parameters of the problem using least squares, we were able to identify baseline soil supply rates and fertilization efficiencies for N and P for each installation. Estimated N supply ranged from 47 kg ha-1 yr-1 to 103 kg ha-1 yr-1, while P supply ranged from 5.5 to 12.4 kg ha-1 yr-1. Fertilization efficiencies were extremely variable, ranging from 23% to 100% for N and 0% to 78% for P. A lower bound to the baseline supply rate was identified for K, Ca, and Mg for each site. While only three sites were P-limited, P limitation was imminent on all sites with operational doses of applied N. While the accuracy of NUTREM is limited by the availability of basic process-level data, the method suggests possibilities for predicting growth response to nutrient amendments. FOR. Sci. 47(1):96–102.

Lipid profiles of Nematocarcinus gracilis a deep-sea shrimp from below the Arabian Sea oxygen minimum zone - Catherine E Allen; Paul A Tyler; Mark S Varney (Hydrobiologia, 2000)

HABITAT SELECTION OF FORAGING BOTTLENOSE DOLPHINS IN RELATION TO BOAT DENSITY NEAR CLEARWATER, FLORIDA - Mark C. Allen; Andrew J. Read (Marine Mammal Science, 2000)

Biological accumulation of 226 Ra in a groundwater‐augmented Florida lake - Mark Brenner; Joseph M. Smoak; Micheal S. Allen; Claire L. Schelske; Douglas A. Leeper (Limnology and Oceanography, 2000)
Round Lake, Hillsborough County, Florida (U.S.A.) has been augmented with 226 Ra‐rich (6.2 dpm L −1 ) groundwater from the Floridan aquifer for more than 30 years. Water column 226 Ra activity in Round Lake is 3.4 dpm L −1 , about one third of the U.S. drinking water standard value. Radionuclide measurements in biota and sediment cores from the lake indicate high 226 Ra activities in plants, mollusc shells and tissues, fish bones, and recent sediments. Unionid mussels bioaccumulate 226 Ra and display very high activities in soft tissues (219.9–454.8 dpm g −1 dry). Throughout Florida, groundwaters are increasingly pumped for agricultural irrigation, as well as residential and industrial use. Biological accumulation of 226 Ra by filter‐feeding pelecypods in aquatic ecosystems is an important pathway for transfer of the radionuclide to higher trophic levels of both aquatic and terrestrial food webs. Radionuclide analysis of soft tissues from aquatic bivalves provides a rapid means of identifying waterbodies that receive substantial inputs of dissolved 226 Ra.

A Jackknife Approach to Examine Uncertainty and Temporal Change in the Spatial Correlation of a VOC Plume - Mark D. Varljen; Michael J. Barcelona; H. Allen Wehrmann (Environmental Monitoring and Assessment, 1999)

Bahamian coral reefs yield evidence of a brief sea-level lowstand during the last interglacial: Reply - Brian White; H. Allen Curran; Mark A. Wilson (Carbonates and Evaporites, 1998)

Bahamian coral reefs yield evidence of a brief sea-level lowstand during the last interglacial - Brian White; H. Allen Curran; Mark A. Wilson (Carbonates and Evaporites, 1998)

Effects of Non-Covalent Self-Association on the Subcutaneous Absorption of a Therapeutic Peptide - Dean K. Clodfelter; Allen H. Pekar; Dawn M. Rebhun; Kevin A. Destrampe; Henry A. Havel; Sharon R. Myers; Mark L. Brader (Pharmaceutical Research, 1998)

Soil fungal‐arthropod responses to Populus tremuloides grown under enriched atmospheric CO 2 under field conditions - JOHN KLIRONOMOS; MATTHIAS RILLIG; MICHAEL ALLEN; DONALD ZAK; MARK KUBISKE; KURT PREGITZER (Global Change Biology, 1997)
We investigated the influence of elevated CO 2 and soil N availability on the growth of arbuscular mycorrhizal and non‐mycorrhizal fungi, and on the number of mycophagous soil microarthropods associated with the roots of Populus tremuloides . CO 2 concentration did not significantly affect percentage infection of Populus roots by mycorrhizal or non‐mycorrhizal fungi. However, the extra‐radical hyphal network was altered both qualitatively and quantitatively, and there was a strong interaction between CO 2 and soil N availability. Under N‐poor soil conditions, elevated CO 2 stimulated hyphal length by arbuscular mycorrhizal fungi, but depressed growth by non‐mycorrhizal fungi. There was no CO 2 effect at high N availability. High N availability stimulated growth by opportunistic saprobic/pathogenic fungi. Soil mites were not affected by any treatment, but collembolan numbers were positively correlated with the increase in non‐mycorrhizal fungi. Results indicate a strong interaction between CO 2 concentration and soil N availability on mycorrhizal functioning and on fungal‐based soil food webs.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Eighteen new polymorphic markers in the multiple endocrine neoplasia type 1 (MEN1) region - Pachiappan Manickam; Siradanahalli C. Guru; Larisa V. Debelenko; Sunita K. Agarwal; Shodimu-Emmanuel Olufemi; Jane M. Weisemann; Mark S. Boguski; Judy S. Crabtree; Yingping Wang; Bruce A. Roe; Irina A. Lubensky; Zhengping Zhuang; et al. (Human Genetics, 1997)

Baroreceptor responses derived from a fundamental concept - Mona F. Taher; Albert B. P. Cecchini; Mark A. Allen; Sherif R. Gobran; Robert C. Gorman; Brian L. Guthrie; Kyle A. Lingenfelter; Sina Y. Rabbany; Philip M. Rolchigo; Julius Melbin; Abraham Noordergraaf (Annals of Biomedical Engineering, 1988)